2021
DOI: 10.1177/14680874211010560
|View full text |Cite
|
Sign up to set email alerts
|

Solid particulate mass and number from ducted fuel injection in an optically accessible diesel engine in skip-fired operation

Abstract: Ducted fuel injection (DFI) is a novel combustion strategy that has been shown to significantly attenuate soot formation in diesel engines. While previous studies have used optical diagnostics and optical filter smoke number methods to show that DFI reduces in-cylinder soot formation and engine-out soot emissions, respectively, this is the first study to measure solid particle number (PN) emissions in addition to particle mass (PM). Furthermore, this study quantitatively evaluates the use of transient particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Novel catalysts control the soluble and non-soluble organic fractions in the engine exhaust. 127,128 DPF 129 efficiency depends on the soot concentration in the incoming exhaust gas stream. 130 Various DPF regeneration strategies oxidize the soot particles collected in the filter at high-temperature conditions.…”
Section: Particulate Emissions Overviewmentioning
confidence: 99%
“…Novel catalysts control the soluble and non-soluble organic fractions in the engine exhaust. 127,128 DPF 129 efficiency depends on the soot concentration in the incoming exhaust gas stream. 130 Various DPF regeneration strategies oxidize the soot particles collected in the filter at high-temperature conditions.…”
Section: Particulate Emissions Overviewmentioning
confidence: 99%
“…This longer mixing length prior to ignition improves the diesel spray's potential to achieve LLFC. Based on early successes, multiple research groups have begun to investigate DFI both experimentally 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and computationally. 7,19,[22][23][24][25][26][27] A number of studies have investigated the impact of duct geometry on DFI combustion in pressure vessels [7][8][9][10][11][12][13]18,26 and engines.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed these flare-ups to spray-spray interactions and/or entrainment of product gases upstream of the established LOL, 2 which likely decrease entrainment and increase soot production. 16,29 Wilmer et al 20 examined soot particle mass and number density from an optical heavy-duty single cylinder research engine for both CDC and DFI conditions at one operating condition using a 4-orifice/4-duct set up. They confirmed that DFI can significantly reduce engine-out soot and showed that DFI both reduces the total number of soot particles as well as their average size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations